PENEGAKAN HUKUM BAGI PEGAWAI NEGERI SIPIL DALAM HUBUNGANNYA DENGAN PERBUATAN PIDANA Studi Koordinasi Antara Penegak Hukum dengan Pemerintah Kabupaten Kendal - Hatnolo Ardi; Sri Endah Wahyuningsih (UNISSULA Semarang, 2019)
In carrying out its duties as a public servant, civil servants throughoutIndonesiamust comply with applicable laws and regulations, including civil servants inKendalDistrict. For civil servants who committed violations and allegedly committed criminal acts, it will be processed by law. Law enforcement within civil servants who commit crimes requires coordination between local government and law enforcement officials. Keywords : Law Enforcement, Civil Servants, and Criminal Acts